Identification of the minimal binding region of a Plasmodium falciparum IgM binding PfEMP1 domain - Semblat, Jean-Philippe (Mol Biochem Parasitol, 2015)
Binding of host immunoglobulin is a common immune evasion mechanism demonstrated by microbial pathogens. Previous work showed that the malaria parasite Plasmodium falciparum binds the Fc-region of human IgM molecules, resulting in a coating of IgM on the surface of infected erythrocytes. IgM binding is a property of P. falciparum strains showing virulence-related phenotypes such as erythrocyte rosetting. The parasite ligands for IgM binding are members of the diverse P. falciparum Erythrocyte Membrane Protein One (PfEMP1) family. However, little is known about the amino acid sequence requirements for IgM binding. Here we studied an IgM binding domain from a rosette-mediating PfEMP1 variant, DBL4ζ of TM284var1, and found that the minimal IgM binding region mapped to the central region of the DBL domain, comprising all of subdomain 2 and adjoining parts of subdomains 1 and 3. Site-directed mutagenesis of charged amino acids within subdomain 2, predicted by molecular modelling to form the IgM binding site, showed no marked effect on IgM binding properties. Overall, this study identifies the minimal IgM binding region of a PfEMP1 domain, and indicates that the existing homology model of PfEMP1-IgM interaction is incorrect. Further work is needed to identify the specific interaction site for IgM within the minimal binding region of PfEMP1.